Strategi Digital Marketing dan Pendampingan Sertifikasi Produk Halal Pelaku Usaha Desa Poreh Kecamatan Lenteng Kabupaten Sampang - Aguilika, Deykha; Faraby, Muhammad Ersya; Makhtum, Ahmad (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
MSMEs in Poreh Village, Lenteng District, Sumenep Regency face challenges in fulfilling business legality and market access, especially related to the lack of understanding of halal certification procedures and low digital literacy in marketing. This community service activity aims to increase the capacity of MSME actors through assistance in the halal certification process and digital marketing strategy training. The methods used include socialization of halal regulations, technical training in managing Business Identification Numbers (NIB) and the SiHalal application, and introducing digital platforms for product promotion. The participatory approach involved MBKM students and the Halal Center of Trunojoyo University, Madura. The activity significantly increases business actors’ understanding of halal certification procedures. Two MSME actors succeeded in obtaining halal certificates through the self-declare scheme after following all stages. In addition, business actors began implementing digital marketing strategies by creating business social media accounts, uploading product content, and reaching consumers outside the village area. Reflections from the activity showed that the combination of practical training and intensive mentoring effectively increased the awareness, skills, and motivation of MSME actors in increasing product competitiveness. Major obstacles, such as low digital literacy and the absence of business legality, were successfully overcome through direct assistance and technical simulations. This activity proves that integrating halal certification and digital marketing is a relevant, applicable, and sustainable empowerment strategy in developing village MSMEs